Identifying the Weights in Exchange Market Pressure - Franc Klaassen (Tinbergen Institute, 2011)
Exchange market pressure (EMP) measures the pressure on a currency to depreciate. It adds to the actual depreciation a weighted combination of policy instruments used to ward off depreciation, such as interest rates and foreign exchange interventions, where the weights are their effectiveness. The key difficulty in the literature is how to identify these weights. We exploit the persistence of pressure and add instruments based on currency crisis theories to identify the weights, and we propose a simple IV regression to estimate them. An application to the European Monetary System crisis in 1992-1993 shows that a one percentage point higher interest rate wards off a depreciation of about 0.2 percent.
Keywords: C26; E42; E58; F31; F33; 330; currency crisis models; ERM crisis; exchange rate regimes; instrumental variables; monetary policy; persistence; Währungskrise; Wechselkurssystem; Abwertung; Eurozone; Instrumentalvariablen-Schätzmethode; EU-Staaten